Unusual presentation of ischiorectal (horseshoe type) abscess - Mahno, Noor Ezmas; Sainal, Yusof; Ong, David; Shabeeb, Fadeel; Md Nor, Azmi (2014)
Ischiorectal abscess is the second most common of anorectal abscess. The most common cause of a peri-anal abscess formation is secondary to anal gland sepsis(1). A third of perianal abscesses may manifest a fistula-in-ano which will increases the risk of abscess recurrence and requiring repeated surgical drainage(2). If it spread further to the right and left ischiorectal space, it will forms a horseshoe’s shape. Case Summary: This is a 21 years old Chinese gentleman with 4 days history of colicky lower abdominal pain and low grade fever. No significant past medical history. Clinically, tenderness felt over left iliac fossa, palpable bladder with bogginess felt per rectal and rectal tenderness at 9 o’clock position. Perianal skin examination looks normal. Blood investigation showed leucocytosis with predominantly neutrophils. Urine examination and abdominal X-ray was unremarkable. Ultrasound abdomen initially was unremarkable but repeated ultrasound on day 3 of admission showed an ill-defined hypoechoic lesion seem to be arising from the rectal wall. Endoanal ultrasound showed horseshoe ischiorectal abscess up to the level of prostate. Subsequently, we proceed with examination under anaesthesia and drainage of abscess on the 7th of January 2014. No perianal fistula seen. Proctoscopy examination was normal. Intraoperatively, we made 2 separate incisions deep into both right and left ischiorectal space with a communicating penrose drain. Culture come back as Escherichia Coli. Antibiotic was completed for 1 week’s course. Postoperative course was uneventful and wound healed well.